An enhanced secondary control approach for voltage restoration in the DC distribution system - Gao, Fei; Wheeler, Patrick; Bozhko, Serhiy (2016)
The paper will deal with the problem of establishing a desirable power sharing in multi-feed electric power system for future more-electric aircraft (MEA) platforms. The MEA is one of the major trends in modern aerospace engineering aiming for reduction of the overall aircraft weight, operation cost and environmental impact. Electrical systems are employed to replace existing hydraulic, pneumatic and mechanical loads. Hence the onboard installed electrical power increases significantly and this results in challenges in the design of electrical power systems (EPS). One of the key paradigms for future MEA EPS architectures assumes high-voltage dc distribution with multiple sources, possibly of different physical nature, feeding the same bus(es). In our study we investigate control approaches to guarantee that the total electric load is shared between the sources in a desirable manner. A novel communication channel based secondary control method is proposed in this paper. Stability of the proposed method is investigated and it proves that the system stability margin is upgraded using the compensation method. The analytical results of the study will be supported by both time-domain simulations and experimental results.